Verbal Response Times as a Potential Indicator of Cognitive Load During Conventional Speech Audiometry With Matrix Sentences. (August 2018) - Meister, Hartmut; Rählmann, Sebastian; Lemke, Ulrike; Besser, Jana
This study examined verbal response times—that is, the duration from stimulus offset to voice onset—as a potential measure of cognitive load during conventional testing of speech-in-noise understanding. Response times were compared with a measure of perceived effort as assessed by listening effort scaling. Three listener groups differing in age and hearing status participated in the study. Testing was done at two target intelligibility levels (80%, 95%) and with two noise types (stationary and fluctuating). Verbal response times reflected effects of intelligibility level, noise type, and listener group. Response times were shorter for 95% compared with 80% target intelligibility, shorter for fluctuating compared with stationary noise, and shorter for young listeners compared with older listeners. Responses were also faster for the older listeners with near normal hearing compared with the older hearing-aid users. In contrast, subjective listening effort scaling predominantly revealed effects of target intelligibility level but did not show consistent noise-type or listener-group effects. These findings show that verbal response times and effort scalings tap into different domains of listening effort. Verbal response times can be easily assessed during conventional speech audiometry and have the potential to show effects beyond performance measures and subjective effort estimates.